3D‐printed cryomilled poly(ε‐caprolactone)/graphene composite scaffolds for bone tissue regeneration. Issue 7 (25th November 2020) - Dias, Daniela; Vale, Ana C.; Cunha, Eunice P. F.; C. Paiva, Maria; Reis, Rui L.; Vaquette, Cedryck; Alves, Natália M.
Abstract: In this study, composite scaffolds based on poly(caprolactone) (PCL) and non‐covalently functionalized few‐layer graphene (FLG) were manufactured by an extrusion‐based system for the first time. For that, functionalized FLG powder was obtained through the evaporation of a functionalized FLG aqueous suspension prepared from a graphite precursor. Cryomilling was shown to be an efficient mixing method, producing a homogeneous dispersion of FLG particles onto the PCL polymeric matrix. Thereafter, fused deposition modeling (FDM) was used to print 3D scaffolds and their morphology, thermal, biodegradability, mechanical, and cytotoxicity properties were analysed. The presence of functionalized FLG demonstrated to induce slight changes in the microstructure of the scaffold, did not affect the thermal stability and enhanced significantly the compressive modulus. The composite scaffolds presented a porosity of around 40% and a mean pore size in the range of 300 μm. The cell viability and proliferation of SaOs‐2 cells were assessed and the results showed good cell viability and long‐term proliferation onto produced composite scaffolds. Therefore, these new FLG/PCL scaffolds comprised adequate morphological, thermal, mechanical, and biological properties to be used in bone tissue regeneration. Abstract :